Deposition and preservation of estuarine sediment, Turnagain Arm, Cook Inlet, Alaska - DeBoer, Darron G. (Kansas State University, 2009)
Turnagain Arm is the hypertidal (commonly exceeding 9 m) west-east trending extension of Cook Inlet in south-central Alaska. The inlet formed from a drowned glacial valley that was subsequently filled with tidal deposits of silt and fine sand. The tidal system is semidiurnal with a prominent diurnal inequality. There are also variations due to spring and neap tides. Turnagain Arm is home to a tidal bore generated during spring tides that can reach heights of up to 2 m and travel at speeds of up to 5 m/s. Current reversals can be dramatic with ebb tidal velocities of 6 m/s changing to flood velocities of 10 m/s over a period of a few minutes. During the initial flood tide, highly turbid water can rise as fast as 10 cm/min. This combination of elements results in a highly dynamic depositional setting. Measurements taken in the inner estuary during several neap-spring cycles in the summers of 2007-08 documented deposition upon mud bars of as much as 8.9 cm per tidal event. Conversely, erosion of up to 13.5 cm per tidal event has been measured. The highest rates of deposition and erosion occurred during the spring tides while much lower rates occur during the neap tides. Some portions of the inner estuary are only submerged during the extreme high tides. The magnitude of the high tide needed to cover each site increases with increasing distance into the upper estuary. Even if submerged, deposition does not always occur. Such a high percentage of non-depositional events has real implications when interpreting tidal cyclicity of the rhythmites found at these sites.
Keywords: estuary; Turnagain Arm; Cook Inlet; hypertidal; tidal sedimentology; rhythmites; Geology (0372)